DAMPAK PENDIDIKAN KEWIRAUSAHAAN MASYARAKAT (PKuM) DALAM KONTEKS PEMBERDAYAAN MASYARAKAT - Entoh Tohani (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2015)
Community Entrepreneurship Education (PKuM) aims at providing the community members to improve the quality of their life. This case study was conducted to identify the economic and social impacts of the PKuM. The research conducted as from April through September 2014 was a qualitative research with the case of PKuM as unit of analysis particularly education programs of Vocational Village developed by Ministry of Education and Culture. In collecting data, the researcher acted as the instrument using interview guides, observation sheets, and document study guide. The data were analyzed qualitatively. The reliability of the data was proved by triangulation and prolonging the observation. The research findings show the positive impacts to the target population though still at individual level. Therefore, the research suggests the PKuM to develop should emphasize its continuity and accountability in empowering the community.